RISK OF THROMBOEMBOLIC AND CARDIOVASCULAR EVENTS ASSOCIATED WITH THE USE OF COMBINED HORMONAL CONTRACEPTIVES (CIPEEX, 2025)
Introduction: The use of combined hormonal contraceptives is associated with an increased risk of thromboembolic events, especially venous thrombosis. Objective: This analysis of the epidemiological and risk situation reviews evidence from case-control studies, cohorts, and systematic reviews, focusing on articles that assess the impact of combined oral contraceptives (COCs) on the risk of venous thromboembolism (VTE), myocardial infarction, and ischemic stroke. Methodology: The authors selected data from multiple sources, including the Cochrane Database of Systematic Reviews (CD011054), scientific articles, and clinical guidelines, extracting information on the type of progestogen, ethinyl estradiol dose, and individual risk factors. Results: The analysis shows that the relative risk of VTE in COC users is 2 to 9 times higher than in non-users, with an estimated absolute risk of approximately 3.5 to 10 cases per 10,000 woman-years. Third- and fourth-generation COCs (such as those containing desogestrel, gestodene, or drospirenone) have a 50–80% higher risk of VTE compared to second-generation COCs (containing levonorgestrel). The risk also increases with ethinyl estradiol doses above 50 µg. In addition, COC use is associated with a two- to three-fold increased risk of ischemic stroke, especially in women with risk factors such as hypertension, smoking, or migraine with aura. The mechanism involves changes in hemostasis, with an increase in procoagulant factors (such as factor VII, X, and fibrinogen) and a reduction in coagulation inhibitors. Despite the methodological limitations of some studies, such as selection bias and inaccurate classification of exposure, the data are consistent in demonstrating a significant increase in cardiovascular risk. Currently, guidelines such as those from the US MEC and EULAR recommend individualized risk profile assessment before prescribing. The authors conclude that, although combined hormonal contraceptives are highly effective, their use requires careful assessment of thrombotic risk factors, prioritizing lower-risk formulations and non-combined alternatives in women with comorbidities or genetic predisposition.
Keywords: Trombosis; Birth control; Hormonal contraceptive; Ischemia